Pelatihan dan Lomba Menulis Cerita Bagi Komunikator Sosial dari Komisi Komunikasi Sosial Keuskupan se-Indonesia - Dharma Oetomo, Budi Sutedjo (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2024)
Stories are a means of conveying messages, advice, teachings, moral values and experiences in a relaxed, captivating and lasting manner on the listeners' hearts. However, telling stories seems to be a skill that only certain people have, so now stories are rarely present in children's bedrooms, classrooms, training or other public spaces. Legendary stories that used to be effective in instilling moral values or introducing the culture of a region no longer seem to increase. This community service activity aims to motivate and equip participants with the knowledge and skills to write stories, so that participants can participate in presenting stories in families, educational spaces and other public spaces. This activity is open to communicators from the Diocesan Social Communication Commission throughout Indonesia and is held online by the Social Communication Commission of the Indonesian Catholic Bishops' Conference. Activities consist of training and competitions. Training is carried out online to motivate, unite perceptions and provide insight into stories. Meanwhile, the competition was held to increase participant involvement. During the training, the participants realized the importance of stories and telling stories. Participants asked many questions to the resource person to deepen the material. They were enthusiastic about writing stories, so several participants sent two stories. Dalam Bahasa Indonesia: Cerita merupakan sarana penyampaian pesan, nasehat, ajaran, nilai-nilai moral maupun pengalaman secara rileks, memikat dan membekas dalam sanubari pendengarnya. Namun, bercerita seolah menjadi keterampilan yang dimiliki orang-orang tertentu saja, sehingga kini cerita sudah jarang hadir di ruang tidur anak, ruang kelas, pelatihan, atau ruang publik lainnya. Cerita-cerita legenda yang dulu efektif untuk menanamkan nilai-nilai moral atau mengenalkan kebudayaan suatu daerah seakan tidak lagi bertambah. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk memotivasi dan membekali peserta dengan pengetahuan dan keterampilan untuk menulis cerita, sehingga peserta dapat berpartisipasi dalam menghadirkan cerita dalam keluarga, ruang pendidikan dan ruang publik lainnya. Kegiatan ini terbuka bagi para komunikator dari Komisi Komunikasi Sosial Keuskupan di seluruh Indonesia dan dilangsungkan secara online oleh Komisi Komunikasi Sosial Konferensi Waligereja Indonesia. Kegiatan terdiri dari pelatihan dan lomba. Pelatihan dilakukan secara online untuk memotivasi, menyatukan persepsi dan memberikan wawasan tentang cerita. Sementara, lomba diadakan untuk meningkatkan keterlibatan peserta. Selama mengikuti pelatihan, para peserta menyadari pentingnya cerita dan bercerita. Banyak pertanyaan yang diberikan peserta kepada narasumber untuk mendalami materi. Mereka antusias untuk menuliskan cerita, sehingga beberapa peserta mengirimkan dua buah cerita.